Research on Detection System for Machinery Parts Based on ZigBee Technology - Liu, Fanjia (International Journal of Mechanical and Electrical Engineering, 2023)
ZigBee technology is a low-power, low-cost, short-range wireless communication technology for various IoT (Internet of Things) applications. Machinery parts detection system monitors the quality, size, shape, and other parameters of machinery parts in real time to ensure the accuracy and quality of the production process. In this article, we propose a machinery parts detection scheme based on ZigBee technology. By deploying wireless sensor networks, the detection data concerning machinery parts could be transmitted in real time, thus reducing the complexity of wiring and improving detection efficiency. ZigBee based machinery parts detection system would provide an efficient and convenient means of detection for the manufacturing industry, thus enjoying a wide range of application prospects.